A INCLUSÃO DE ALUNOS COM DEFICIÊNCIA NA ESCOLA PÚBLICA DE ENSINO MÉDIO: em foco o Projeto Político Pedagógico do Centro de Ensino Médio Liceu Maranhense - Brito, Silvana Maria dos Anjos Pires (2013)
This academic investigative research was motivated by the urgent demand to understand and apply educational praxis to favor the development of educational proposals for disabled students aiming to promote their potential development through programs, actions, resources and diversified professional performances according to their needs from 2008 on, when special education is taken under the inclusion perspective through decrees, resolutions and technical citations. When inclusive praxis is reflected in schools some questions arise, also considered investigative issues in this academic research, such as: How is the inclusion of disabled students being taken into effect at high schools? How is this inclusion being cleared up in the Political-Pedagogical Project, written and applied in the school where the student is enrolled? Having as its general purpose the analysis of the disabled students inclusion focusing the Centro de Ensino Liceu Maranhense Political-Pedagogical Project and as specific goals the description of the legal and institutional statutory which support the propositions to disabled students education in Maranhão; to discuss the inclusion conception stated in the official documents, highlighting its principles and identifying these conceptions along the Political-Pedagogical Project construction and implementation as well as the attitudes that make the inclusion process possible. The theoretical support for the analysis and reflections is based on Baptista (2006); Bueno (2008); Ferreira and Ferreira (2004); Fontes (2009); Glat and Blanco (2009); Mendes and Almeida (2010); Prieto (2010), written papers organized by VEIGA and other authors about Political-Pedagogical Project enrich the theoretical reference of this research, which used Bardin, 2011 to analyze the content of the written Political-Pedagogical Project for its methodological position contributing to a qualitative research. Also interviews with the school principal, the pedagogy coordinators, students and teachers who work with disabled students and special education tutors were used to complement the analysis and inferences. The reached results reveal that the institution political project is characterized as a regulation description in which disabled students school inclusion appears as a rule of law, not intrinsically related to the educational praxis applied in day-by-day basis.